Nitrate-Enrichment Structures Phytoplankton Communities in the Shallow Eastern Mediterranean Coastal Waters - Rahav, Eyal; Raveh, Ofrat; Yanuka-Golub, Keren; Belkin, Natalia; Astrahan, Peleg; Maayani, Meor; Tsumi, Noam; Kiro, Yael; Herut, Barak; Silverman, Jacob; Angel, Dror L. (Frontiers in Marine Science, 2020)
Submarine groundwater discharge (SGD) has been shown to be an important source of nutrients in coastal environments, especially nitrogen and silica, and thereby relive nutrient limitation to phytoplankton. Here, we followed autotrophic microbial biomass, activity, and community composition at a site strongly influenced by SGD and a nearby nutrients-poor reference site at the oligotrophic Israeli shallow rocky coast [southeastern Mediterranean Sea (SEMS)] between 2011 and 2019. The surface water at the SGD-affected area had significantly higher NO3 + NO2 (∼10-fold) and Si(OH)4 (∼2-fold) levels compared to the reference site, while no significant differences were observed for PO4 or NH4. This resulted in a significant increase in algae biomass (∼3.5-fold), which was attributed to elevated Synechococcus (∼3.5-fold) and picoeukaryotes (∼2-fold) at the SGD-affected site, and in elevated primary production rates (∼2.5-fold). Contrary to most SGD-affected coastal areas, diatoms biomass remained unchanged between sites, despite the elevated N and Si, suggesting the dominance of picophytoplankton over microphytoplankton at the SEMS. DNA sequencing of the 16S and 18S rDNA supported these findings. These results highlight the influence of SGD on shallow-water microbial populations. Our observations are consistent with recent studies showing that phytoplankton along the Israeli coast are likely nitrogen + silica limited, and may have important ecological and regulatory implications for environmental policy and management of coastal aquifers.